The Asymmetric Impact of Trade Openness on Inflation in Sudan - Elhassan, Tomader Gaber Elbasheer (Asian Economic and Financial Review, 2020)
This study examines the asymmetric impact of openness on inflation in Sudan from 1970 to 2018. This study is distinguished from previous studies applied in Sudan because it employed the trade Globalization Index to measure openness instead of the traditional index. The data were collected from the Central Bank of Sudan and the KOF Swiss Economic Institute website. The nonlinear auto-regressive distributive lag (NARDL) was also employed to examine the asymmetric impact of openness on inflation in Sudan. The results showed that the positive shocks in the openness in the short- and long-terms increased the inflation rate. The negative shocks in the openness in the short term decreased the inflation rate. However, the negative shocks in openness in the long-term did not have an effect on inflation rate. The study recommends a focus on production for self-sufficiency and exports to reduce the inflation rate. In addition, policymakers in Sudan should implement more policies to support openness and control inflation.